Neurophysiological Indicators of Residual Cognitive Capacity in the Minimally Conscious State. (4th October 2015) - Hauger, Solveig L.; Schnakers, Caroline; Andersson, Stein; Becker, Frank; Moberget, Torgeir; Giacino, Joseph T.; Schanke, Anne-Kristine; Løvstad, Marianne
Abstract : Background . The diagnostic usefulness of electrophysiological methods in assessing disorders of consciousness (DoC) remains to be established on an individual patient level, and there is need to determine what constitutes robust experimental paradigm to elicit electrophysiological indices of covert cognitive capacity. Objectives . Two tasks encompassing active and passive conditions were explored in an event-related potentials (ERP) study. The task robustness was studied in healthy controls, and their utility to detect covert signs of command-following on an individual patient level was investigated in patients in a minimally conscious state (MCS). Methods . Twenty healthy controls and 20 MCS patients participated. The active tasks included (1) listening for a change of pitch in the subject's own name (SON) and (2) counting SON, both contrasted to passive conditions. Midline ERPs are reported. Results . A larger P3 response was detected in the counting task compared to active listening to pitch change in the healthy controls. On an individual level, the counting task revealed a higher rate of responders among both healthy subjects and MCS patients. Conclusion . ERP paradigms involving actively counting SON represent a robust paradigm in probing for volitional cognition in minimally conscious patients and add important diagnostic information in some patients.